An Education in Exploitation: Chinese International Secondary School Students and the Dark Side of International Education - Liu, Helen (Journal of International Students, 2023)
Canada’s international education system is highly unregulated, with many recruitment agencies and homestay services taking agency in providing these services to students, leaving them vulnerable and open to exploitation. Furthermore, many school boards often do not take responsibility in arranging these services for international students, resulting in a lack of accountability that can further contribute to a cycle of deceit and students navigating this process with limited knowledge or oversight. Utilizing international student security (ISS), this article draws on interviews with six Canadian secondary school teachers from and two Chinese international secondary school students all located in Toronto and the Greater Toronto Area (GTA) to reveal the profitability of international students, and the exploitative nature of international student services providers like recruitment agencies and homestay companies. Ultimately, the article identifies responsible key stakeholders and beneficial institutional and policy improvements to better regulate international education and protect these vulnerable international youth.